Pregnancy and Postpartum Bowel Changes: Constipation and Fecal Incontinence. (April 2015) - Shin, Grace Hewon; Toto, Erin Lucinda; Schey, Ron
Abstract : N/A: Pregnancy and the postpartum period are often associated with many gastrointestinal complaints, including nausea, vomiting, and heartburn; however, the most troublesome complaints in some women are defecatory disorders such as constipation and fecal incontinence, especially postpartum. These disorders are often multifactorial in etiology, and many studies have looked to see what risk factors lead to these complications. This review discusses the current knowledge of pelvic floor and anorectal physiology, especially during pregnancy, and reviews the current literature on causes and treatments of postpartum bowel symptoms of constipation and fecal incontinence.